Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1038/32695
|View full text |Cite
|
Sign up to set email alerts
|

Role of calcineurin and Mpk1 in regulating the onset of mitosis in budding yeast

Abstract: Signalling via calcium is probably involved in regulating eukaryotic cell proliferation, but details of its mechanism of action are unknown. In Schizosaccharomyces pombe, the onset of mitosis is determined by activation of a complex of the p34cdc2 protein kinase and a cyclin protein that is specific to the G2 phase of the cell cycle. This activation requires dephosphorylation of p34cdc2. Weel, a tyrosine kinase that inhibits p34cdc2 by phosphorylating it, is needed to determine the length of G2 phase. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
157
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(166 citation statements)
references
References 24 publications
7
157
2
Order By: Relevance
“…The functions of ESP1, CLB2, MIH1 and CDC20 as regulators of mitosis have been extensively characterized (Baum et al, 1988;Russell et al, 1989;Sethi et al, 1991;Surana et al, 1991;Visintin et al, 1997;Ciosk et al, 1998;Shirayama et al, 1998;Uhlmann et al, 1999). ZDS2 and ZDS1 are required for G 2 /M progression and SWE1 function and can suppress mutations in numerous genes, mostly cell cycle regulators (Bi and Pringle, 1996;Ma et al, 1996;Schwer and Shuman, 1996;Yu et al, 1996;Mizunuma et al, 1998;Roy and Runge, 2000, and references within). DHH1 is a non-essential DEAD-box helicase that has been implicated in SWE1 function (Strahl-Bolsinger and Tanner, 1993;Warbick and Glover, 1994;Moriya and Isono, 1999), translation (Ladomery et al, 1997), transcription (Hata et al, 1998) and cell cycle arrest under stressful conditions (Maekawa et al, 1994;Bergkessel and Reese, unpublished).…”
Section: Isolation Of High Copy Suppressors Of the Taf68-9 Mutantmentioning
confidence: 99%
See 1 more Smart Citation
“…The functions of ESP1, CLB2, MIH1 and CDC20 as regulators of mitosis have been extensively characterized (Baum et al, 1988;Russell et al, 1989;Sethi et al, 1991;Surana et al, 1991;Visintin et al, 1997;Ciosk et al, 1998;Shirayama et al, 1998;Uhlmann et al, 1999). ZDS2 and ZDS1 are required for G 2 /M progression and SWE1 function and can suppress mutations in numerous genes, mostly cell cycle regulators (Bi and Pringle, 1996;Ma et al, 1996;Schwer and Shuman, 1996;Yu et al, 1996;Mizunuma et al, 1998;Roy and Runge, 2000, and references within). DHH1 is a non-essential DEAD-box helicase that has been implicated in SWE1 function (Strahl-Bolsinger and Tanner, 1993;Warbick and Glover, 1994;Moriya and Isono, 1999), translation (Ladomery et al, 1997), transcription (Hata et al, 1998) and cell cycle arrest under stressful conditions (Maekawa et al, 1994;Bergkessel and Reese, unpublished).…”
Section: Isolation Of High Copy Suppressors Of the Taf68-9 Mutantmentioning
confidence: 99%
“…The predicted outcomes of the overexpression of ZDS2, CLB2, ZDS1 and MIH1 would be an increase in G 2 /M cyclin-dependent kinase activity and the increased rate of G 2 /M progression. ZDS2 and ZDS1 are likely positive regulators of the cell cycle (Bi and Pringle, 1996;Ma et al, 1996;Yu et al, 1996;Mizunuma et al, 1998) by inhibiting the function of SWE1, a negative regulator of mitosis (Booher et al, 1993). CLB2 is a mitotic cyclin, and overexpression will directly enhance CDK activity (Surana et al, 1991).…”
Section: Genetic Links Between Tafs and Cdksmentioning
confidence: 99%
“…1A, B). As Erk5 activity has been associated with cell cycle progression, 14,24 we synchronised the cells in G1/S phase by incubating them with thymidine and then stained them with propidium iodide (PI) for cytofluorometric evaluation of the cell cycle. The PI profiles showed that a fraction of shErk5 cells were polyploid (Fig.…”
Section: Thymidine Generates Lethal Dna Damage In Erk5-depleted Jurkamentioning
confidence: 99%
“…Mck1p plays a role in mitotic chromosomal segregation specific to CDEIII function (Shero and Hieter, 1991), acts in the transcription of IME1 at the beginning of meiosis (Neigeborn and Mitchell, 1991), and is important for inducing the cell cycle delay in response to Ca 2ϩ (Mizunuma et al, 2001). Mds1p/Rim11p plays a role in expression of meiotic genes by phosphorylating Ime1p and Ume6p (Bowdish et al, 1994;Xiao and Mitchell, 2000).…”
Section: Introductionmentioning
confidence: 99%